Structural modifications in Bermuda grass [Cynodon dactylon (L.) Pers.] ecotypes for adaptation to environmental heterogeneity - Aasma Tufail; Farooq Ahmad; Mansoor Hameed; Muhammad Ahsan; Mohammad K. Okla; Umme Habibah Siddiqua; Noreen Khalid; Madiha Rashid; Anis Ali Shah; Momtaz M. Hegab; Hamada AbdElgawad (Frontiers in Plant Science, 2023)
IntroductionIt is well known that different ecotypes adopt different mechanisms to survive under environmental stress conditions. In this regard, each ecotype showed different type of modifications for their existence in a specific habitat that reflects to their ecological success.MethodsHere, differently adapted ecotypes of Bermuda grass [Cynodon dactylon (L.) Pers.] were collected to evaluate their differential structural and functional modifications that are specific to cope with environmental stress conditions. The soil that adheres ecotypes roots were highly saline in case of DF-SD (Derawar Fort-Saline Desert), UL-HS (Ucchali Lake-Hyper Saline) and G-SSA (Gatwala-Saline Semiarid) ecotypes. Soils of S- HS (Sahianwala-Hyper Saline), S-SW (Sahianwala-Saline Wetland) and PA-RF (Pakka Anna-Reclaimed Field) were basic (pH 9 to 10). Soils of UL-HS and PA- HS (Pakka Anna-Hyper Saline), KKL-S (Kalar Kahar Lake-Saline), BG-NS (Botanic Garden-Non Saline) and G-SSA were rich in organic matter, and soil of BG-NS and DF-SD were rich in minerals. Anatomical modifications were performed by using the free hand sectioning technique and light microscopy.Results and DiscussionDF-SD is one of the best ecotypes which showed anatomical modifications to cope with environmental changes. These modifications included stem cross-sectional area and leaf sheath thickness that contribute towards water storage, vascular tissues for proficient translocation of solutes and trichomes that provide resistance to water loss. On the other hand, sclerification in root is the only notable modification in the Gatwala Saline Semiarid (G-SSA) ecotype from saline arid habitat where rainfall is not as low as in the Cholistan Desert. Two ecotypes from hyper-saline wetlands, UL-HS and KL-HS showed increased number and size of vascular tissue, central cavity and sclerification in stem which are important for solutes conduction, water loss and salts bulk movement, respectively. The ecotype from reclaimed site was not much different from its counterpart from hyper-saline dryland. Overall, anatomical modifications to maintain water conservation are key mechanisms that have been identified as mediating stress tolerance in C. dactylon ecotypes.